Quantification of parasite burden of Trypanosoma cruzi and identification of Discrete Typing Units (DTUs) in blood samples of Latin American immigrants residing in Barcelona, Spain - Tavares de Oliveira, Maykon; Sulleiro, Elena; Silgado Gimenez, Aroa; de Lana, Marta; Zingales, Bianca; Santana da Silva, João; Marin-Neto, J. Antônio; Molina, Israel (PLOS Neglected Tropical Diseases, 2020)
Background Trypanosoma cruzi has a high genetic and biological diversity and has been subdivided into seven genetic lineages, named TcI-TcVI and TcBat. DTUs TcI-TcII-TcV and TcVI are agents of ChD in different regions of Latin America. Due to population movements, the disease is an emergent global public health problem. Thus, the aim of this study was to quantify the parasitic load and identify the presence of T. cruzi DTUs in 101 Latin American immigrants with chronic ChD, residing in Barcelona, Spain. Methodology / Principal findings 5ml of peripheral blood were collected in guanidine/EDTA from each patient for DNA extraction, quantification of the parasitic load and genotyping. A great variation of the parasitic load of the patients was verified: from 0.001 to 22.2 T. cruzi DNA (fg) / Blood DNA (ng). In patients from Bolivia the parasitic load was 3.76±4.43 T. cruzi DNA (fg) / Blood DNA (ng) (mean ± SD), in patients of other countries was 0.95±1.38 T. cruzi DNA (fg) / Blood DNA (ng). No statistically significant difference was observed in the parasitic load between patients with the indeterminate and cardiac forms of ChD (p = 0,57). Parasite genotyping was performed by multilocus conventional PCR. In patients from Bolivia there was a nearly equal prevalence of DTUs TcV (27/77), TcII/TcV/TcVI (26/77), and TcII/TcVI (22/77). TcVI was detected in only 2 samples (2/77). A higher prevalence of TcII/TcVI (19/24) was verified in patients of other countries, with low prevalence of TcII/TcV/TcVI (4/24) and TcV (1/24). Conclusions/Significance In this study, low/medium parasitic load was found in all patients evaluated. Our data corroborate previous conclusions indicating that patients from the Bolivia, living in Spain, are predominantly infected by TcV, and TcVI DTUs. On the other hand, in Non-Bolivians patients TcII/TcVI predominated. Surprisingly, in our cohort of 101 patients no infection by TcI DTU was observed.